Preparation and Evaluation of Natural Gum-Based Immediate Release Metformin Hydrochloride Tablet (Bangladesh Pharmaceutical Journal, 2018)
Metformin hydrochloride is a first line BCS class III oral anti-diabetic drug used for the treatment of type 2 diabetes. The main goal of this study was to formulate, prepare and evaluate natural gum-based immediate release metformin hydrochloride tablet. Seven different formulations of compressed tablets were prepared following wet granulation process using different concentrations (10, 20, 30, 50, 60, 70, 80 and 90 mg) of Aegle marmelos gum as a binder. Aegle marmelos gum is a biodegradable natural gum which is economic, easily available and found useful as tablet binder for both conventional and novel dosage forms. Other excipients used in the formulation were microcrystalline cellulose (MCC), croscarmellose sodium (CCS), maize starch, colloidal silicon dioxide (CSD), sodium starch glycolate (SSG), magnesium stearate etc. In the present study, the compressed tablets were evaluated for weight variation, thickness, hardness, friability, disintegration time and dissolution. In vitro drug release study was carried out in phosphate buffer (pH 6.8) at 37 ± 0.5oC with 50 rpm using USP Dissolution Apparatus 2-Paddle method. The flowability of granules for all the batches was optimum which reflected in the bulk density and angle of repose. It can be concluded from this study that combination of Aegle marmelos as a binder with other excipients can be prospectively used in the preparation of metformin hydrochloride immediate release (IR) tablet.Bangladesh Pharmaceutical Journal 21(2): 101-108, 2018